Insolvency Proceedings: ASEAN and EU Comparison on the Rules of Foreign Court Jurisdiction - Anggriawan, Rizaldy (Indonesian Comparative Law Review, 2020)
Due to a lack of uniformity or harmonization of laws and regulations, cross-border insolvency has remained an issue in the ASEAN region. ASEAN economic openness with the implementation of the ASEAN Free Trade Area (AFTA) and ASEAN Economic Community (AEC) may create issues at some points as investors compete to dominate the ASEAN while assets are located not only on their own territory but also in other ASEAN member countries. On some occasions, they can fail to meet their debt payment obligations when performing international business transactions. As a result of the bankruptcy case, a legal arrangement may exist between the country in which the business actor is declared bankrupt and the country in which the bankrupt debtor's assets are located. This interaction between two or more countries involves a clash of jurisdictions. In order to counter such an issue, ASEAN may learn from what the EU has done over these decades. The study aims to compare the regulatory issue of foreign court jurisdiction in settling the insolvency cases both in ASEAN and EU. The paper is normative-qualitative legal research. It used a comparative, statute, and conceptual approach. It is found that in terms of cross-border insolvency, the European Union is far ahead of ASEAN, given that at least two major regulations in place, namely EC Regulation 1346/2000 and EU Regulation 2015/848, while ASEAN has almost nothing to offer at this time. The experience of the EU to formulate and implement a settled regulation on foreign court jurisdiction in settling the insolvency cases among EU member countries is one of the valuable lessons that ASEAN may take from the EU.